Morphological Characteristics of the Kidneys on the 14th and 21th Days during the Prolonged Period of Moderate Brain Injury - Khuseynovna, Khuseynova Gulshan (Journal of Science in Medicine and Life, 2023)
This article presents information about the results of scientific studies that allow to evaluate and study the morphological features of the kidneys of 3-month-old rats after moderately severe brain injuries. Morphological analysis of rat kidneys was performed on days 14 and 21 after brain injury.